PENGEMBANGAN BUKU AJAR BERBASIS LOKAL MATERI KEANEKARAGAMAN LABA-LABA DI KOTA METRO SEBAGAI SUMBER BELAJAR ALTERNATIF BIOLOGI UNTUK SISWA SMA KELAS X - Suwarni, Erna (Bioedukasi Jurnal Pendidikan Biologi, 2015)
The textbook is one of learning resources that can be developed by teachers in learning activities. Textbook lesson in the form of material substance systematically arranged to show the integrity of the competencies that will be controlled by learners in learning activities. Textbooks can assist teachers in delivering learning materials in order to achieve learning objectives. The purpose of this research is to develop locally-based textbook on materials spider diversity in Metro City as a source of alternative learning biology, knowing the quality of textbooks based on the qualifications of matter, pedagogy, and legibility, as well as to study the response of students to textbooks and cognitive outcomes. Product specification expected in this study is a locally-based textbook that can be used as a biologyâs alternative learning resource that can measure cognitive learning outcomes. This study uses research and development with 4D development model developed by S. Thiagarajan et al, which consists of four stages of development that define, design, develop, and disseminate. Data obtained from tests of cognitive learning outcomes in the form of tabulated data to test the validity, reliability, and homogeneity with SPSS 16.0 so that it can be known whether there is a difference in average learning outcomes pre-test and post-test that uses a textbook and do not use textbooks by using t-test. The calculation data using t-test average yield obtained on the control class that does not use the textbook is 7.03 and the class textbook treatment using the results obtained an average of 8.10. Conclusion: textbook produced has been validated by the user and learning experts, and fit for use. And there is the difference in average learning outcomes of students between class control and class treatment.Kata Kunci: Buku ajar, keanekaragaman, sumber belajarÂ